Hydrothermal reduction of carbon dioxide to low-carbon fuels - Jin, Fangming (CRC Press, Taylor & Francis Group, 2018)
The book covers advances in hydrothermal reduction of CO2 into low-carbon fuels. It offers perspectives from chemical engineering, environmental chemicals, organic chemistry, inorganic chemistry, physical chemistry, geology and materials science. It addresses fundamentals and applications of hydrothermal chemical processes, associated materials, and technologies. It describes reduction with biomass and dissociation of water by solar energy-driven two-step process. Challenges and strategies are discussed to facilitate research and development.